Revitalizing Umbul Tlatar: A Strategic Plan for Post-COVID Tourism Recovery - Saputra, Aditya; Danardono; Sunariya, M Iqbal Taufiqurrahman; Prasetyo, Ari; Setiawan, Ilyas Nur; Farida, Rahma Afifah Nur; Altair, Garin Rachmad; Rahmadi, Dinda Putri (Universitas Muhammadiyah Surakarta, 2024)
The Umbul Tlatar area is a water tourism destination with considerable potential. Its proximity to the city of Surakarta, good accessibility, and abundant surface water resources makes it an attractive site for bathing and water sports. However, the lack of a defined tourism concept and development planning, as well as the absence of an integrative approach, has resulted in the area appearing underdeveloped and poorly maintained. This has led to suboptimal tourist appeal, with fluctuating visitor numbers, particularly in the post-COVID-19 period (2023–2024). Therefore, there is a need for a strategic development plan to maximize the tourism potential of Umbul Tlatar, enabling it to compete with other tourist destinations in Boyolali Regency and the surrounding areas. The objective of study us to construct integrative tourism planning in Umbul Tlatar. The combination drone mapping and field observation was conducted to obtain the hidden potency of Umbul Tlatar. The results shows that the Umbbul Tlatar has several tourism attcraction that could be developed more such as Umbul Pengilon, National standar swimming pool, Etasia-Ecotourism, Tlatar Cullinary, Sumber Rejeki Fishing pond, and Karunia Outbound Centre. Those several tourism spots will be planned as integrated tourism area, thus at least can extend the tourist time to stay. To address this, a collaborative effort between the local government and community is required to develop an integrative tourism site plan that can increase visitor numbers to Umbul Tlatar.